2008
DOI: 10.1073/pnas.0804583105
|View full text |Cite
|
Sign up to set email alerts
|

A loss of function allele for murine Staufen1 leads to impairment of dendritic Staufen1-RNP delivery and dendritic spine morphogenesis

Abstract: The dsRNA-binding protein Staufen was the first RNA-binding protein proven to play a role in RNA localization in Drosophila. A mammalian homolog, Staufen1 (Stau1), has been implicated in dendritic RNA localization in neurons, translational control, and mRNA decay. However, the precise mechanisms by which it fulfills these specific roles are only partially understood. To determine its physiological functions, the murine Stau1 gene was disrupted by homologous recombination. Homozygous stau1 tm1Apa mutant mice ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 25 publications
4
145
1
Order By: Relevance
“…Like many RNA-binding factors, the Drosophila and mammalian Staufen proteins have been implicated in multiple post-transcriptional processes including alternative splicing 13 , RNA localization 4,6,[30][31][32] , translational activation 7 and translation-dependent mRNA decay [8][9][10][11]14,20,33,34 . Which activity is observed depends on the cellular context, the identity of the bound RNA and the location of the binding site on the target RNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like many RNA-binding factors, the Drosophila and mammalian Staufen proteins have been implicated in multiple post-transcriptional processes including alternative splicing 13 , RNA localization 4,6,[30][31][32] , translational activation 7 and translation-dependent mRNA decay [8][9][10][11]14,20,33,34 . Which activity is observed depends on the cellular context, the identity of the bound RNA and the location of the binding site on the target RNA.…”
Section: Discussionmentioning
confidence: 99%
“…FMRP, however, is a negative regulator of translation. Whereas deletion of either FMRP or Stau1 causes neurological defects, the phenotypes are opposite: absence of FMRP leads to dendritic spine overgrowth 46 , whereas absence of Stau1 results in fewer spines 14 . Thus it is possible that FMRP and Stau1 have opposing roles in synaptic protein production, with FMRP inhibiting translation and Stau1 promoting it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single detection was performed as described previously (Vessey et al, 2008). For the simultaneous detection of two transcripts, differentially labeled RNA probes (DIG and fluorescein) are allowed to hybridize together to their targets at 65°C overnight.…”
Section: Fluorescent Ish With Tyramide Signal Amplificationmentioning
confidence: 99%
“…55,76 Expression of a dominant negative form of staufen results in inhibition of RNA transport to dendrites, 77 and neurons from knockout mice are deficient in dendritic delivery of RNPs while the mice themselves show defects in locomotor activity. 78 Mammalian staufen has four double-stranded RNA binding domains, although not all of them have strong doublestranded RNA binding activity. 54 Besides a preference for double-stranded RNA, staufen has long been thought to be relatively nonspecific in its RNA binding, but recent work has demonstrated that staufen may in fact prefer distinct double-stranded structures.…”
Section: Zbp1mentioning
confidence: 99%